The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1097/fjc.0b013e3181f04b1c
|View full text |Cite
|
Sign up to set email alerts
|

20-Hydroxyeicosatetraeonic Acid: A New Target for the Treatment of Hypertension

Abstract: Arachidonic acid (AA) is metabolized by enzymes of the CYP4A and 4F families to 20-hydroxyeicosatetraeonic acid (20-HETE) which plays an important role in the regulation of renal function, vascular tone and the long term control of arterial pressure. In the vasculature, 20-HETE is a potent vasoconstrictor and upregulation of the production of this compound contributes to the elevation in oxidative stress, endothelial dysfunction and the increase in peripheral vascular resistance associated with some forms of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
180
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(189 citation statements)
references
References 169 publications
7
180
1
1
Order By: Relevance
“…[20][21][22] In parallel, we demonstrate that the renal content of 20-HETE exhibits a clear circadian pattern and that this pattern is significantly modified in kidneys of clock(2/2) mice. 20-HETE has a potent prohypertensive effect by acting as a vasoconstrictor of preglomerular arterioles, but it can also inhibit several important sodium transporters in the proximal tubule and the thick ascending limb (Na + -K + -adenosine triphosphatase, NHE3, NKCC2 Na 1 -K + -Cl 2 cotransporter 2), [23][24][25][26] thereby promoting sodium excretion and lowering BP.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…[20][21][22] In parallel, we demonstrate that the renal content of 20-HETE exhibits a clear circadian pattern and that this pattern is significantly modified in kidneys of clock(2/2) mice. 20-HETE has a potent prohypertensive effect by acting as a vasoconstrictor of preglomerular arterioles, but it can also inhibit several important sodium transporters in the proximal tubule and the thick ascending limb (Na + -K + -adenosine triphosphatase, NHE3, NKCC2 Na 1 -K + -Cl 2 cotransporter 2), [23][24][25][26] thereby promoting sodium excretion and lowering BP.…”
Section: Discussionmentioning
confidence: 57%
“…Indeed, drugs targeting the 20-HETE axis present an interesting therapeutic potential for vascular and salt-sensitive hypertension, acute kidney injury, and renal cancer. 22,29,30 Some of these compounds are being tested in preclinical studies. 22 The circadian rhythmicity of 20-HETE levels indicates that the safety and efficiency of these drugs could vary depending on the time they are administered.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that closure of BK Ca accounts for the remaining BP effects of 20-HETE in the male TRPV1 KO and female WT mice, rather than to its documented effects on renal sodium transport. 22 Importantly, differences in BK Ca expression and activity have been previously excluded as underlying sex differences in vascular reactivity. 25 The activity of 20-HETE at TRPV1 is likely to be a phenomenon common to several vascular beds innervated by sensory C-fibers, including the coronary 26 and splanchnic 27 circulations.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,22 The exact molecular pathways mediating the vasoactive effects of 20-HETE are uncertain: a fact particularly compounded by the lack of identification, to date, of a credible receptor for this ligand. 20-HETE-induced phosphorylation of smooth muscle BK Ca , resulting in channel closure, is thought to mediate, in part, 20-HETE-induced constriction, although direct binding of 20-HETE to BK Ca has not been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…604426) encodes an ω-hydroxylase that catalyzes the metabolism of arachidonic acid to 20-hydroxyeicosatetraenoic acid (20-HETE) (1). Previous studies have demonstrated that 20-HETE has two contradictory effects in the development of hypertension (2,3). One is prohypertension resulting from constriction of the small arteries (4,5).…”
Section: Introductionmentioning
confidence: 99%